Pengaruh Citra Destinasi dan Fasilitas Wisata pada Minat Kunjung Wisatawan Taman Margasatwa Ragunan - Saragi, Charles Parnauli; Prahmana, Shafa Putri; Utami, Nisa Rahmaniah (Prasetiya Mulya Publishing, 2025)
Jakarta is one of the cities that has a lot of tourism potential, one of which is educational tourism in Ragunan Wildlife Park. A good tourist destination requires a determining factor for success such as destination image so that tourists are interested in making repeat visits. In the midst of tight competition because many new tourist destinations have emerged, managers must pay attention to tourist facilities so that tourists are interested in making repeat visits. The purpose of this study was to determine the effect of destination image and tourist facilities on the interest of repeat tourists at the Ragunan Wildlife Park tourist attraction. This study used a quantitative method with multiple linear regression analysis. The sampling technique used purposive sampling with a sample size of 105 respondents. The analysis techniques used were instrument testing, classical assumption testing, and hypothesis testing using IBM SPSS Statistics 25 software. The results of this study indicate that: 1) Destination Image partially has a positive and significant effect on the interest in repeat visits to the Ragunan Wildlife Park tourist attraction. 2) Tourist facilities partially have a positive and significant effect on the interest in repeat visits to the Ragunan Wildlife Park tourist attraction. 3) Destination image and tourist facilities simultaneously have a positive and significant influence on the interest in repeat visits to the Ragunan Wildlife Park tourist attraction.